Demographic and psychological predictors of recovery from coronary artery bypass graft - Sadeghi, Mehran (J Educ Health Promot, 2017)
OBJECTIVES: Worldwide, i.e. in Iran, coronary artery bypass grafting (CABG) is one of the most common and expensive surgeries. This study was designed to explore the demographic and psychological factors which predict the recovery process in CABG patients. MATERIALS AND METHODS: During a prospective correlational study, 250 CABG patients, in two public and private hospitals, investigated for indexes of recovery during hospital stay and 4 weeks after discharge. Demographic and psychological variables were collected through checklist and Farsi validated and reliable versions of type D personality, the multidimensional scale of perceived social support, revised illness perception questionnaire (IPQ-R). Data were analyzed through statistical tests through SPSS version 20. RESULTS: Considering the total recovery index, 91.2% of CABG patients have not been recovered 4 weeks after surgery. Furthermore, 99% of them reported high scores of depression and anxiety. Marital and insurance status, and perceived personal control, showed significant difference between recovered and unrecovered patients based on total recovery index (P < 0.05); however, in regression analysis, they did not identify as predictor variables. Age, gender, insurance status, and perceived personal control were the most frequent variables identified as predictors of recovery indexes, separately. CONCLUSION: The correlation between depression, anxiety, perceived personal control, and recovery status among our patients reveals the importance of considering psychological and mood assessment in developing guidelines for CABG patients. Our findings will assist clinicians for designing of psychological interventions for promotion of perceived personal and illness control and better recovery post-CABG.